Taxonomic Structure Evolution, Chemical Composition and Anaerobic Digestibility of Microalgae-Bacterial Granular Sludge (M-BGS) Grown during Treatment of Digestate - Joanna Kazimierowicz; Marcin Dębowski; Marcin Zieliński (Applied Sciences, 2023)
The liquid fraction from the dewatering of digested sewage sludge (LF-DSS) represents a major processing complication for wastewater treatment facilities, thus necessitating new and effective methods of LF-DSS neutralization. This pilot-scale study examined the evolution of a Chlorella sp. monoculture into microalgal-bacterial granular sludge (M-BGS) during treatment of LF-DSS in a hybrid photo-bioreactor (H-PBR). The M-BGS reached a stable taxonomic and morphological structure after 60 days of H-PBR operation. The biomass was primarily composed of Chlorella sp., Microthrix parvicella, and type 1851 and 1701 filamentous bacteria. A greater abundance of bacteria led to a faster-growing M-BGS biomass (to a level of 4800 ± 503 mgTS/dm3), as well as improved TOC and COD removal from the LF-DSS (88.2 ± 7.2% and 84.1 ± 5.1%). The efficiency of N/P removal was comparable, since regardless of the composition and concentration of biomass, it ranged from 68.9 ± 3.1% to 71.3 ± 3.1% for N and from 54.2 ± 4.1% to 56, 2 ± 4.6% for P. As the M-BGS taxonomic structure evolved and the C/N ratio improved, so did the anaerobic digestion (AD) performance. Biogas yield from the M-BGS peaked at 531 ± 38 cm3/gVS (methane fraction = 66.2 ± 2.7%). It was found that final effects of AD were also strongly correlated with the N and TOC content in the substrate and pH value. A mature M-BGS significantly improved settleability and separability through filtration.